Enforcement Effectiveness Traffic Violations By Electronic Traffic Law Enforcement ( ETLE ) at Polrestabes Semarang Jurisdiction - Bagus Setiyono (Jurnal Penelitian Pendidikan, 2024)
The development of digital technology and government policies taken due to the Covid 19 Pandemic is still on going makeTraffic Police in Indonesia uses the ETLE system in terms of violation enforcement. There are various obstacles that cause violation cannot be fully detected and result in traffic accidents that are still happening.